2015
DOI: 10.1016/j.mad.2015.06.003
|View full text |Cite
|
Sign up to set email alerts
|

On the complex relationship between energy expenditure and longevity: Reconciling the contradictory empirical results with a simple theoretical model

Abstract: The relationship between energy expenditure and longevity has been a central theme in aging studies. Empirical studies have yielded controversial results, which cannot be reconciled by existing theories. In this paper, we present a simple theoretical model based on first principles of energy conservation and allometric scaling laws. The model takes into considerations the energy tradeoffs between life history traits and the efficiency of the energy utilization, and offers quantitative and qualitative explanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 119 publications
(201 reference statements)
1
39
0
Order By: Relevance
“…It should also be kept in mind that metabolic rate is not necessarily a direct readout of the use of ATP to prevent aging. Hou has applied quantitative modeling coupled to experimental data to clarify that the lifespan outcome can depend on the type of process metabolic output is applied to . In these models, predominantly shuttling metabolic output to biosynthesis, such as organismal development, precludes its use in bolstering repair processes that combat cellular aging.…”
Section: An Emerging Paradigm: the Energy Maintenance Theory Of Agingmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be kept in mind that metabolic rate is not necessarily a direct readout of the use of ATP to prevent aging. Hou has applied quantitative modeling coupled to experimental data to clarify that the lifespan outcome can depend on the type of process metabolic output is applied to . In these models, predominantly shuttling metabolic output to biosynthesis, such as organismal development, precludes its use in bolstering repair processes that combat cellular aging.…”
Section: An Emerging Paradigm: the Energy Maintenance Theory Of Agingmentioning
confidence: 99%
“…There is no inverse relationship between life span and mass‐specific metabolic rates in mice or fruit flies . Larger dog breeds usually have shorter lifespan than smaller dogs despite smaller dogs having higher rates of energy metabolism . Species of garter snake with higher metabolism and ATP levels live longer than species that have lower metabolism .…”
Section: Compatibility Of the Emta With Other Theories Of Agingmentioning
confidence: 99%
“…

In this issue of BioEssays, Chaudhari and Kipreos hypothesize that mitochondrial fusion promotes survival, especially in old animals, through the mechanism of maintaining energy metabolism. Also, caloric restriction (CR) extends lifespan, but does not lower energy consumption greatly.As cited in Chaudhari and Kipreos, the results from Hou et al [2,3] have suggested that cellular damage is insensitive to the change in total energy consumption. Interestingly, the 10th pathway upregulates alternate energy generating pathways; third, maintaining ATP levels and energy metabolism supports longevity.

Practitioners in the relevant fields may have three questions about this hypothesis.

…”
mentioning
confidence: 94%
“…As cited in Chaudhari and Kipreos, the results from Hou et al [2,3] have suggested that cellular damage is insensitive to the change in total energy consumption. It is the energy allocation to damage repair (or maintenance in general) that largely influences the damage level and aging rate.…”
mentioning
confidence: 94%
See 1 more Smart Citation